How perceptions of firm environmental and social values influence frontline employee outcomes. Issue 7 (31st July 2020) - Gabler, Colin B.; Landers, V. Myles; Rapp, Adam
Abstract : Purpose: More than ever, consideration of the natural environment and social welfare are values that firms must signal to their stakeholders. One way to do this is by adopting an environmental orientation (EO) and pro-social organizational identity (PSOI). The purpose of this paper is to examine how frontline employees (FLEs) respond to these firm-level values through four outcomes. Design/methodology/approach: Polynomial structural equation modeling with response surface analysis was implemented on FLEs survey data to uncover how different levels of EO and PSOI impact sales performance, word-of-mouth, turnover intent and job satisfaction. Findings: Both firm-level values have a positive and direct effect on all four outcomes. However, each imposes a boundary condition as well. Specifically, salespeople perform better when their firm has a stronger EO, but they are happier in their work, less likely to quit and more likely to spread positive word-of-mouth when PSOI is stronger. Practical implications: The results suggest that perceptions of a firm-level EO or PSOI enhance employee-level outcomes. Signaling to employees that your firm cares about the natural environment and the greater social good positively influences employee outcomes, but optimization of each outcome depends on the strength of those values. Originality/value: This research answers two specific research calls. First, it applies signaling theory to the workplace context, positioning FLEs as the receivers and feedback mechanisms of firm-level signals. Second, using too-much-of-a-good-thing logic, it uncovers boundary conditions imposed by social and environmental constructs on frontline outcomes.